Legal Implications for Regulating Investigation Authority in Accident Cases at Railroad Crossings - Erifendi Churniawan; Handoko U; Ainun fikria (Unram Law Review, 2021)
The purpose of this research is to find out the legal implications of regulating the investigative authority in cases of accidents at railroad crossings. The research method used in this study is normative juridical research using a statutory approach, and a conceptual approach. The results obtained from this study are the implications arising from different provisions of Law Number 22 of 2009 concerning Road Traffic and Transportation, and Law Number 23 of 2007 concerning Railways is that there is a tug of war on the authority of investigation between related agencies, namely Police Investigators and Railway PPNS. The tug-of-war of this investigative authority resulted in a conflict of investigative authority, where Police investigators conducted investigations based on the provisions of the Criminal Code, while the Railway PPNS conducted investigations based on the provisions of Law Number 23 of 2007 concerning Railways.